The effects of working time reductions on wages, actual hours and equilibrium unemployment - Oskar Nordström Skans (Institute for Labour Market Policy Evaluation (IFAU), 2001)
This paper extends a general equilibrium model of unemployment and working hours and evaluates the model on a 5 percent working time reduction for shift workers in Sweden. Panel data from firms' payroll records are used to examine the relationship between standard hours, actual hours and hourly wages. The main results are: i) Actual hours only decreased by 40 percent of the reduction in standard hours. ii) Hourly wages for shift workers rose relative to wages for daytime workers. iii) The wage increase was more pronounced for workers who received a larger reduction of actual hours. The conclusion is that working time reductions that allow for discretion on lower levels of bargaining do not necessarily reduce actual hours. Furthermore, working time reductions may result in an increase in wage pressure, causing unemployment to rise.
Keywords: E24; J22; J23; J51; 330; Work sharing; working hours; unemployment; wage pressure